Optimasi Proses Ekstraksi Bunga Telang (Clitoria ternatea) Berbantu Gelombang Mikro Menggunakan Aplikasi Response Surface Methodology - Rini Azharini; Asri Widyasanti; Siti Nurhasanah (Agricultural Faculty, 2022)
Butterfly pea (Clitoria ternatea) had a variety of active compounds that was the potential an alternative source of natural antioxidants. Procedures for isolating active compounds could been through microwave-assisted extraction. The purpose of this research was to found out the combination of solvent volume treatment, extraction time, and microwave power that produces optimum yield and analysis of extract quality characteristics. Microwave-assisted extraction process used 10 g of butterfly pea powder with a solvent volume of 150 ml to 250 ml, extraction time of 3 minutes to 7 minutes, and power by 30% to 70%. This study used the experimental methods and optimization processes with The Respon Surface Methodology (RSM) type Box-Behnken Design (BBD). Optimum conditions of the extraction process were obtained with a solvent volume of 196 ml for 3 minutes, and microwave power of 30%. The yield optimal response result was obtained by 53.39%, residual ethanol was 30.17%, total flavonoid compounds was 60.77 mgQE/g, specific gravity 1.082, pH 4.33 and color analysis L* 14.93, a* 0.14, b* -0.56, chromatic 0.56, hue 284.63 (Blue Purple), and TCD was in very different categories. This study analyzed that microwave-assisted extraction with variable solvent volume, time, and power affects the yield and quality characteristics of the extracts.